Reversion of lethality and growth defects in Fatiga oxygen-sensor mutant flies by loss of Hypoxia-Inducible Factor-α/Sima - Centanin, L. (2005)
Hypoxia-Inducible Factor (HIF) prolyl hydroxylase domains (PHDs) have been proposed to act as sensors that have an important role in oxygen homeostasis. In the presence of oxygen, they hydroxylate two specific prolyl residues in HIF-α polypeptides, thereby promoting their proteasomal degradation. So far, however, the developmental consequences of the inactivation of PHDs in higher metazoans have not been reported. Here, we describe novel loss-of-function mutants of fatiga, the gene encoding the Drosophila PHD oxygen sensor, which manifest growth defects and lethality. We also report a null mutation in dHIF-α/sima, which is unable to adapt to hypoxia but is fully viable in normoxic conditions. Strikingly, loss-of-function mutations of sima rescued the developmental defects observed in fatiga mutants and enabled survival to adulthood. These results indicate that the main functions of Fatiga in development, including control of cell size, involve the regulation of dHIF/Sima. © 2005 European Molecular Biology Organization.